1989
DOI: 10.1002/ijc.2910430111
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between nasopharyngeal carcinoma and high antibody titers to epstein‐barr virus‐specific thymidine kinase

Abstract: Epstein-Barr virus (EBV) has long been implicated in nasopharyngeal carcinoma (NPC). Recent studies in our and other laboratories have shown a correlation between the disease and high antibody titers to EBV-specific DNase. These data led us to also examine serial sera from healthy adults and patients with infectious mononucleosis or NPC, for their capacity to neutralize the EBV-specific thymidine kinase (TK) activity from chemically induced EBV-carrying human lymphoblastoid cells. Our results were the followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…In both tests, sera from NPC patients were shown to have a high level of antibody to the EBV TK; furthermore, if the tests were designed to detect IgA antibody, then the reaction was specific to sera from NPC patients. These results extend the findings of Turenne-Tessier et al (1989), who showed that sera from NPC patients could neutralize the enzymatic activity of the EBV TK. We describe here a method of detecting IgA antibody to EBV-coded enzymes, which is a valuable combination for diagnosis of NPC.…”
Section: Serum Numbersupporting
confidence: 90%
See 2 more Smart Citations
“…In both tests, sera from NPC patients were shown to have a high level of antibody to the EBV TK; furthermore, if the tests were designed to detect IgA antibody, then the reaction was specific to sera from NPC patients. These results extend the findings of Turenne-Tessier et al (1989), who showed that sera from NPC patients could neutralize the enzymatic activity of the EBV TK. We describe here a method of detecting IgA antibody to EBV-coded enzymes, which is a valuable combination for diagnosis of NPC.…”
Section: Serum Numbersupporting
confidence: 90%
“…There are several reports that EBV-coded enzymes, including the alkaline DNase, DNA polymerase, and more recently the TK, are specifically neutralized by sera from NPC patients (Cheng et al, 1980;Liu et al, 1989;Turenne-Tessier et al, 1989). We were interested to see if the recombinant TK could act as a target in Western blots to detect anti-TK reactivity in sera from NPC patients.…”
Section: Western Blot Analysis Of Tkmentioning
confidence: 99%
See 1 more Smart Citation
“…NPC patients may also make antibody to the EBV TK [28]. Patients with infectious mononucleosis (IM), chronic active EBV infection, and patients infected with HIV have elevated antibody titers to EBV-encoded dUTPase [12].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with infectious mononucleosis (IM), chronic active EBV infection, and patients infected with HIV have elevated antibody titers to EBV-encoded dUTPase [12]. While the unique antibody patterns to these EBV proteins (or other herpes virus proteins) and other EBV-encoded proteins have been found to be clinically useful [1], [28]–[30], the underlying factor(s) that produce these antibody patterns to EBV proteins and the role these proteins might play in the pathophysiology of EBV-associated disease, separate from their role in the replication of the virus, is still being explored. There have not been many studies to determine whether EBV-encoded proteins expressed during lytic and/or abortive-lytic replication have immunoregulatory properties.…”
Section: Discussionmentioning
confidence: 99%